Pengaruh Leverage, Operating Capacity, Firm Size, Dan Operating Cash Flow Terhadap Financial Distress - Hani, Michelle; Viriany, Viriany (Fakultas Ekonomi Universitas Gresik, 2023)
This study was conducted with the aim of demonstrating and empirically testing the impact of leverage, operating capacity, firm size and operating cash flow on financial distress. The population used in this study are manufacturing companies in the plastic and packaging sub-sector, listed on the Indonesia Stock Exchange from 2019 to 2022. Through the purposeful sampling technique, 38 data samples were collected for the study and will be further analyzed by multiple regression analysis technique. The approach for gathering data makes use of secondary information from yearly financial reports from www.idx.co.id. Research results demonstrate that leverage has a significant positive effect on financial distress, operational capacity has a significant negative effect on financial distress, while firm size and operating cash flow has no significant effect on financial distress.